Location Information-Based Routing Protocol for Energy Harvesting Cognitive Radio Wireless Sensor Network - Mohamad-Rida Mortada; Abbass Nasser; Alaaeddine Ramadan; Koffi-Clement Yao; Ali Mansour (IEEE Access)
This paper explores the integration of Location Information-based Routing (LIBRO) protocol into Energy Harvesting-based Cognitive Radio Wireless Sensor Networks (EH-CWSNs) to address energy consumption challenges and ensure sustainable operation. LIBRO has been recently proposed as an efficient routing algorithm for traditional WSN networks. In this paper, we extend its application to EH-CWSNs, in which the WSN nodes act as Secondary Users (SUs). By proposing LIBRO-based EH-CWSN, we aim to eliminate energy constraints on the nodes and reduce the need for frequent battery replacements in EH-CWSN, thus enabling deployment in challenging environments. Additionally, LIBRO’s unique feature of minimizing nodes’ cooperation during routing offers advantages for protecting Primary Users (PUs) against interference caused by secondary transmissions. The paper’s primary goal is to adapt LIBRO to the CWSN functionalities, especially the spectrum sensing operation. Then, EH-CWSN network parameters are optimized to ensure lower energy consumption compared to the harvested energy from EH units, establishing a sustainable network while respecting PU collision limits. Through a multi-objective optimization approach, we seek to strike a balance between collision probability with PUs, energy consumption, packet delivery latency, and network throughput, creating a self-powered network that meets various constraints. Numerical findings demonstrate the effectiveness of LIBRO in enhancing energy and spectral efficiencies in EH-CWSNs compared to state-of-the-art routing protocols.